Submarine Groundwater Discharge and Stream Baseflow Sustain Pesticide and Nutrient Fluxes in Faga'alu Bay, American Samoa - Welch, Eric M.; Dulai, Henrietta; El-Kadi, Aly; Shuler, Christopher K. (Frontiers in Environmental Science, 2019)
It is increasingly recognized that groundwater discharge in the form of stream baseflow and submarine groundwater discharge (SGD) plays an important role in contaminant transport. This study seeks to demonstrate the importance of groundwater flow for the distribution and transport of selected pesticides and nutrients in the Faga`alu aquifer on the island of Tutuila in American Samoa. Field measurements, including seepage runs and analysis of stream and groundwater for pesticides and nutrients, were combined with hydrological modeling. Selected analytes were glyphosate (GLY), dichlorodiphenyl-trichloroethane (DDT), imidacloprid, and azoxystrobin for pesticides and chemical species of nitrogen, phosphate, and silicate for nutrients. Hydrological flow and transport models of the aquifer were built to simulate groundwater flow and to provide estimates of GLY and dissolved inorganic nitrogen (DIN) fluxes. Stream baseflow was responsible for 59% and SGD for 41% of groundwater flow to the bay, which totaled 6,550 m3/d in the dry season when surface runoff was negligible. DDT was found in 85% and GLY in 100% of tested samples. SGD and baseflow thus delivered 9 g/d of DDT, 0.9 g/d of GLY, 570 g/d of DIN and 840 g/d of dissolved inorganic phosphorus (DIP) into Faga’alu Bay. While all pesticide levels are below environmental limits, their presence in baseflow and SGD, which discharge continuously year-round, result in sustained fluxes of GLY and DDT to the reef. The presence of DDT in groundwater decades after its last application confirms its long-term environmental persistence.